COVID-19 Vaccine Acceptance among Health Care Workers in the Kingdom of Saudi Arabia - Jad A. Elharake, MPH; Bayan Galal; Saleh A. Alqahtani, MD; Rana F. Kattan, MD, MME; Mazin A. Barry, MD; Mohamad-Hani Temsah, MD; Amyn A. Malik, MBBS, MPH, PhD; SarahAnn M. McFadden, PhD, RN, CPN; Inci Yildirim, MD, PhD, MSc; Kaveh Khoshnood, PhD; Saad B. Omer, MBBS, MPH, PhD, FIDSA; Ziad A. Memish, MD, FACP, FRCPC, FRCPE, FIDSA (International Journal of Infectious Diseases, 2021)
Objectives: The purpose of our study was to assess COVID-19 vaccine acceptance among health care workers (HCWs) in the Kingdom of Saudi Arabia (KSA) and identify: 1) vaccine acceptance barriers; 2) demographic differences; and 3) the most trusted COVID-19 sources of information. Methods: Between October and December 2020, all registered HCWs in the KSA were emailed a survey questionnaire, using Qualtrics® and Google Forms®, evaluating their acceptance of a COVID-19 vaccine. Results: Of the 23,582 participants surveyed, 15,299 (64.9%) said they would accept a COVID-19 vaccine. Vaccine acceptance among HCWs differed by several demographic characteristics, with males (69.7%), Christians (71.9%), and Pakistanis (81.6%) most likely to accept a COVID-19 vaccine. Of the 8,202 (35.1%) who said they would not accept a COVID-19 vaccine, the main reason reported was fear of potential side effects (58.5%). Participants reported health officials (84.6%) as the most reliable source of COVID-19 information. Additionally, participants reported the highest confidence in the KSA Ministry of Health (88.5%). Conclusions: Overall, these findings provide KSA health care authorities with the information needed to develop public health messaging campaigns for HCWs to best address COVID-19 vaccine concerns—especially as the country prepares to vaccinate its general population.